Politics and Agricultural Policy Implementation in Tanzania - Kawishe, Palme Thadey; Mallya, Ernest Theobald (Universitas Brawijaya, 2022)
Despite the fact that there is high agricultural policy density in Tanzania, implementation of the agricultural policies has remained ineffective. Studies to explain the causes of implementation ineffectiveness are vast. However, the political dimension of agricultural policy implementation is seldom systematically examined. Thus politics as a variable that can steer implementation has hitherto received a narrow focus. The article examines how the political dynamic has led to ineffective agricultural policy implementation in Tanzania. The article applies qualitative research methods. We used in-depth interviews with key agricultural and political stakeholders to uncover the effects of politics on agricultural policy implementation. Empirical data shows that the implementation of agricultural policies in Tanzania is vastly affected by politics. Politics has affected the allocation of resources required for effective policy implementation. The paper has also noted incidences of political capture in the form of threats, political interference, imprecise prioritisation, resource diversion, rent-seeking and embezzlement of policy implementation resources. Our analysis shows that politics matters in policy implementation. Politics has been a source of implementation disruptions when it is misapplied. This article champions the body of knowledge on the policy-politics dichotomy by arguing that applying politics rightly in the policy process can reduce implementation disruptions.